Formulation And Evaluation Of Channa Striatus Extract And Fusidic Acid Aerosol For Treatment Of Wounds And Burn - Febriyenti, Febriyenti (2011)
Aerosol is a new drug delivery system for wound dressing and wound treatment. Aerosol has several benefits when compared with other delivery systems such as plasters or bandages for wound dressing and cream or gel for wound treatment. When applied to the body aerosol reduces pain that may result from the mechanical rubbing of gel and creams onto the skin. Aerosol could cover any size of wound which could not be covered by films due to films have a fixed size. Channa striatus has been used since a long time ago traditionally to accelerate the wound healing.